A comparative study and analysis of the amended foreign employment income exemption in South Africa - Essop, Ahmed (University of the Witwatersrand, Johannesburg, 2023)
Tax exemptions are granted by the government for a multitude of reasons. These include providing some form of tax relief, alleviating specifically identified tax burdens, encouraging investment, promoting donations to approved public benefit organizations and avoiding the possibility of double taxation (Kransdorff, 2010, p. 79). One specific provision in section 10(1)(o)(ii) of the South African Income Tax Act of 1962, pertained to South African residents working abroad, namely the foreign employment income exemption. The intention of this exemption was to prevent residents from being double taxed (SARS, 2021a). Over the last few years, there has been a noted increase in the number of South Africans working abroad and this has been alluded to as being one of the reasons that government decided to review and amend the section 10(1)(o)(ii) foreign employment income exemption (Ryan, 2020). The impact of this amendment on South African residents working abroad will be analysed and investigated. A comparative analysis will be done on the tax payable of South African residents working in the following countries: the UK, the UAE and India
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (Specialising in Taxation) to the Faculty of Commerce, Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2023
Keywords: Tax exemption; Double taxation; Foreign income; Double tax agreements; Tax havens; Income Tax Act 58 of 1962 (‘the Tax Act’); Section 6quat rebate; Foreign employment income exemption; UCTD; SDG-8: Decent work and economic growth